Positive electrode material and preparation method thereof, positive plate and lithium-sulfur battery

The transition metal sulfide derived from MOF material and SPAN in situ recombination, solves the problems of low sulfur load and insufficient conductivity in lithium-sulfur batteries, and achieves a positive electrode material with high sulfur load, high circulation and low resistivity, which significantly Improves the electrochemical performance of lithium-sulfur batteries.

CN119153645APending Publication Date: 2024-12-17中汽新能(天津)电池科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411147376.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

During the charging and discharging process, lithium-sulfur batteries have self-discharge and depletion of active substances due to the generation of soluble lithium polysulfides, and the conductivity of the active materials is limited, and volume expansion during circulation is limited, which limits their application progress.

Method used

The transition metal sulfide derived from MOF material is used to recombine with SPAN in situ. By regulating the addition of transition metal types and surface additives, SPAN-based composite materials with high sulfur load, high cycle, high magnification and low resistivity are synthesized as the positive electrode. Material, used for the positive electrode of lithium sulfur battery.

Benefits of technology

It significantly improves the electrochemical performance of lithium-sulfur batteries, improves sulfur load, cycle stability and electrochemical reaction kinetics, and improves long cycle performance and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153645A_ABST
    Figure CN119153645A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a positive electrode material and a preparation method thereof, a positive plate and a lithium-sulfur battery. The preparation method of the positive electrode material comprises the following steps: (1) uniformly mixing polyacrylonitrile, transition metal salt and CTAB (Cetyltrimethyl Ammonium Bromide) in an organic solvent to obtain a solution A; dissolving 2-methylimidazole into an organic solvent to obtain a solution B; adding the solution B into the solution A to obtain ZIF-PAN; and 2) mixing the ZIF-PAN with sulfur powder, then carrying out ball milling, drying, and then carrying out calcination treatment to obtain the positive electrode material. According to the invention, transition metal sulfide derived from the MOF material is compounded with SPAN in situ, and the SPAN-based composite material with high sulfur loading capacity, high cycle, high magnification and low resistivity is synthesized as the positive electrode material by regulating the type of transition metal and the addition amount of a surface additive and utilizing the advantages of the MOF material that the morphology is regular and adjustable and the like, and is used for the positive electrode of a lithium-sulfur battery, so that the service life of the lithium-sulfur battery is prolonged, and the service life of the lithium-sulfur battery is prolonged. The electrochemical performance is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular relates to a positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium-sulfur battery. Background Art

[0002] Lithium-sulfur batteries have exciting potential for application in next-generation secondary battery systems due to their high theoretical specific capacity (1675 mAh g-1) and high theoretical specific energy (2600 Wh / kg) produced by multi-electron reactions. However, the practical application of lithium-ion batteries still faces challenges, especially the generation of soluble lithium polysulfides (Li PSs) during charge and discharge operations. The repeated diffusion and reaction of Li PSs between the positive and negative electrodes lead to significant self-discharge and depletion of active materials. In addition, the limited conductivity of active materials and the volume expansion that occurs during cycling pose additional obstacles to the progress of lithium-sulfur batteries.

[0003] Among the many types of sulfur positive electrode materials, sulfurized polyacrylonitrile (SPAN) material has a unique reaction mechanism and excellent electrochemical performance as a positive electrode for lithium-sulfur batteries. SPAN has a very high reversible capacity. Since it exhibits a non-dissolving solid-solid conversion mechanism in carbonate solvents, there will be no shuttling of lithium polysulfide, and it has excellent cycle stability and extremely high coulombic efficiency. However, it still has problems such as slow electrochemical reaction kinetics, low sulfur loading, and poor high-rate performance on the road to commercialization. CN112759874B discloses a preparation method for improving the electrochemical performance of SPAN materials by Se doping, but the Se-doped SPAN positive electrode material has a low sulfur loading and low specific capacity, and its performance still has a lot of room for improvement. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium-sulfur battery.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a positive electrode material comprises the following steps: 1) mixing polyacrylonitrile, a transition metal salt and CTAB in an organic solvent to obtain a liquid A; dissolving 2-methylimidazole in the organic solvent to obtain a liquid B; adding the liquid B to the liquid A to obtain ZIF-PAN; and 2) mixing the ZIF-PAN with sulfur powder, ball milling the mixture, drying the mixture and calcining the mixture to obtain the positive electrode material.

[0007] The transition metal salt is one of zinc nitrate hexahydrate and cobalt nitrate hexahydrate or a mixture of the two.

[0008] In step 1), the mass ratio of CTAB to transition metal salt is (1-4): (2-100); preferably (1-4): (8-12); more preferably 1:8;

[0009] The mass ratio of transition metal salt, 2-methylimidazole and polyacrylonitrile is (4-6): (10-30): (20-100); preferably (4-6): 20: (20-100), and more preferably 4:20:40.

[0010] In step 3), the mass ratio of Z IF-PAN to sulfur powder is 1:(3-10), preferably 1:5.

[0011] The calcination step in step 3) is heat treatment at 300-450° C. for 2-10 hours.

[0012] In step 1), the organic solvent is methanol or DMF. The molecular weight of the polyacrylonitrile is 50,000 to 500,000 g / mol.

[0013] The method for preparing the positive electrode material further comprises step 4) removing the surface sulfur; specifically, heating in a nitrogen atmosphere at 150-250° C. for 5-20 hours.

[0014] The present invention also includes a positive electrode material obtained by the preparation method.

[0015] The present invention also includes a positive electrode sheet, comprising the positive electrode material, a conductive agent and a binder;

[0016] Preferably, the conductive agent is super-p; preferably, the binder is PVDF;

[0017] Preferably, the positive electrode sheet is prepared by the following method: the positive electrode material, the conductive agent and the binder are uniformly mixed to prepare a slurry, and then the slurry is uniformly coated on an aluminum foil, dried, and cut to obtain the positive electrode sheet.

[0018] The present invention also includes a lithium-sulfur battery, comprising the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention utilizes transition metal sulfides derived from MOF materials and SPAN for in-situ compounding. By regulating the type of transition metals and the amount of surface additives added, the advantages of MOF materials such as adjustable morphology rules are utilized to synthesize SPAN-based composite materials with high sulfur loading, high cycle, high rate and low resistivity as positive electrode materials for lithium-sulfur battery positive electrodes, thereby significantly improving their electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 2 are the EIS curves of Examples 1 and 2 and Comparative Example 1. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0023] Example 1

[0024] A method for preparing a positive electrode material comprises the following steps: 1) firstly dissolving 4g polyacrylonitrile (150000g / mol, the same below), 0.4g zinc nitrate hexahydrate, and 0.05g CTAB in 40ml organic solvent DMF (the same below) and mixing; in addition, taking 2g of 2-methylimidazole, dissolving it in 40ml organic solvent DMF (the same below), and adding it to the former solution to obtain ZIF-8-PAN. 2) adding the obtained ZIF-8-PAN and sulfur powder into ethanol in a mass ratio of 1:5, ball milling, and then drying; heat treating the dried mixture at 350°C for 3 hours, and then cooling it naturally to room temperature to obtain a composite material; 3) removing the surface floating sulfur in a nitrogen atmosphere at 155°C for 10 hours, and obtaining the composite material ZnS-SPAN positive electrode material after natural cooling.

[0025] A method for preparing a positive electrode sheet comprises the following steps: uniformly mixing ZnS-SPAN, super-p and PVDF in a mass ratio of 8:1:1 to prepare a slurry, then uniformly coating the slurry on an aluminum foil, vacuum drying at 60°C, and cutting into positive electrode sheets of ф10; the positive electrode sheets of the following embodiments and comparative examples have the same preparation method, the only difference being that the positive electrode materials are different.

[0026] A preparation method of a lithium-sulfur battery comprises the following steps: using Celgard 2500 as a diaphragm, dissolving 1M lithium hexafluorophosphate (Li PF6) in dimethyl carbonate (DMC), ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio of 1:1:1) as an electrolyte, the negative electrode material is a metal lithium sheet, the positive electrode sheet is assembled into a CR2032 type button battery, numbered battery 1, and the battery preparation methods of the following embodiments and comparative examples are the same, and the only difference is that the positive electrode sheet is different.

[0027] Example 2

[0028] A method for preparing a positive electrode material comprises the following steps: 1) firstly dissolving 4g of polyacrylonitrile, 0.4g of cobalt nitrate hexahydrate, and 0.05g of CTAB in DMF and mixing well; taking 2g of 2-methylimidazole, dissolving it in an organic solvent, and adding it to the former solution to obtain ZIF-67-PAN. 2) adding the obtained ZIF-67-PAN and sulfur powder in a mass ratio of 1:5 into ethanol for ball milling, and then drying; heat treating the dried mixture at 350°C for 3 hours, and then cooling it naturally to room temperature to obtain a composite material; 3) removing the floating sulfur on the surface under a nitrogen atmosphere at 155°C for 10 hours, and obtaining the composite material CoS2-SPAN positive electrode material after natural cooling.

[0029] CoS2-SPAN, super-p and PVDF were prepared into positive electrode sheets in a mass ratio of 8:1:1 and assembled into CR2032 button batteries, numbered as battery 2.

[0030] Example 3

[0031] A method for preparing a positive electrode material comprises the following steps: 1) firstly dissolve 4g polyacrylonitrile, 0.2g zinc nitrate hexahydrate, 0.2g cobalt nitrate hexahydrate, and 0.05g CTAB in DMF and mix well; in addition, take 2g 2-methylimidazole, dissolve it in an organic solvent, and add it to the former solution to obtain ZIF-8 / 67-PAN. 2) add the obtained ZIF-8 / 67-PAN and sulfur powder in ethanol in a mass ratio of 1:5, and then ball mill, and then dry; heat treat the dried mixture at 350°C for 3 hours, and then naturally cool to room temperature to obtain a composite material; 3) then remove the floating sulfur on the surface in a nitrogen atmosphere at 155°C for 10 hours, and obtain the composite material ZnS-CoS2-SPAN positive electrode material after natural cooling.

[0032] ZnS-CoS2-SPAN, super-p and PVDF were prepared into positive electrode sheets in a mass ratio of 8:1:1 and assembled into CR2032 button batteries, numbered as battery 3.

[0033] Example 4

[0034] A method for preparing a positive electrode material comprises the following steps: 1) firstly dissolving 4g of polyacrylonitrile, 0.4g of cobalt nitrate hexahydrate, and 0.2g of CTAB in DMF and mixing well; taking 2g of 2-methylimidazole, dissolving it in an organic solvent, and adding it to the former solution to obtain ZIF-67-PAN. 2) adding the obtained ZIF-67-PAN and sulfur powder in a mass ratio of 1:5 into ethanol for ball milling, and then drying; heat treating the dried mixture at 350°C for 3 hours, and then cooling it naturally to room temperature to obtain a composite material; 3) removing the floating sulfur on the surface in a nitrogen atmosphere at 155°C for 10 hours, and obtaining the composite material CoS2-SPAN positive electrode material after natural cooling.

[0035] CoS2-SPAN, super-p and PVDF were prepared into positive electrode sheets in a mass ratio of 8:1:1 and assembled into CR2032 button batteries, numbered as battery 4.

[0036] Example 5

[0037] A method for preparing a positive electrode material comprises the following steps: 1) firstly dissolving 10g of polyacrylonitrile, 0.4g of cobalt nitrate hexahydrate, and 0.05g of CTAB in DMF and mixing well; in addition, taking 2g of 2-methylimidazole, dissolving it in an organic solvent, and adding it to the former solution to obtain ZIF-67-PAN. 2) adding the obtained ZIF-67-PAN and sulfur powder in a mass ratio of 1:5 into ethanol for ball milling, and then drying; heat treating the dried mixture at 350°C for 3 hours, and then cooling it naturally to room temperature to obtain a composite material; 3) then removing the floating sulfur on the surface under a nitrogen atmosphere at 155°C for 10 hours, and obtaining the composite material CoS2-SPAN positive electrode material after natural cooling.

[0038] CoS2-SPAN, super-p and PVDF were prepared into positive electrode sheets in a mass ratio of 8:1:1 and assembled into CR2032 button batteries, numbered as battery 5.

[0039] Example 6

[0040] A method for preparing a positive electrode material comprises the following steps: 1) firstly dissolving 2g of polyacrylonitrile, 0.4g of cobalt nitrate hexahydrate, and 0.05g of CTAB in DMF and mixing evenly; taking 2g of 2-methylimidazole, dissolving it in an organic solvent, and adding it to the former solution to obtain ZIF-67-PAN. 2) adding the obtained ZIF-67-PAN and sulfur powder in a mass ratio of 1:5 into ethanol for ball milling, and then drying; heat treating the dried mixture at 350°C for 3 hours, and then cooling it naturally to room temperature to obtain a composite material; 3) removing the floating sulfur on the surface in a nitrogen atmosphere at 155°C for 10 hours, and obtaining the composite material CoS2-SPAN positive electrode material after natural cooling.

[0041] CoS2-SPAN, super-p and PVDF were prepared into positive electrode sheets in a mass ratio of 8:1:1 and assembled into CR2032 button batteries, numbered as battery 6.

[0042] Example 7

[0043] A method for preparing a positive electrode material comprises the following steps: 1) firstly dissolving 4g of polyacrylonitrile, 0.4g of zinc nitrate hexahydrate, 0.2g of cobalt nitrate hexahydrate, and 0.05g of CTAB in DMF and mixing; in addition, taking 2g of 2-methylimidazole, dissolving it in an organic solvent, and adding it to the former solution to obtain ZIF-8 / 67-PAN. 2) adding the obtained ZIF-8 / 67-PAN and sulfur powder in ethanol in a mass ratio of 1:5, ball milling, and then drying; heat treating the dried mixture at 350°C for 3 hours, and then naturally cooling to room temperature to obtain a composite material; 3) then removing the floating sulfur on the surface in a nitrogen atmosphere at 155°C for 10 hours, and naturally cooling to obtain a composite material ZnS-CoS2-SPAN positive electrode material.

[0044] ZnS-CoS2-SPAN, super-p and PVDF were prepared into positive electrode sheets in a mass ratio of 8:1:1 and assembled into CR2032 button batteries, numbered as battery 7.

[0045] Comparison sample 1

[0046] First, 4g of polyacrylonitrile was mixed with sulfur powder in a mass ratio of 1:5 and added to ethanol for ball milling, and then dried; the dried mixture was heat treated at 350℃ for 3 hours, and then naturally cooled to room temperature to obtain a composite material, and then removed the surface sulfur in a nitrogen atmosphere at 155℃ for 10 hours, and the composite SPAN positive electrode material was obtained after natural cooling. SPAN, super-p, and PVDF were prepared as positive electrodes in a mass ratio of 8:1:1, and assembled into a CR2032 button battery, numbered battery 8.

[0047] Table 1 shows the sulfur loading data of Examples 1-7 and Comparative Example 1. It can be seen from Table 1 that the sulfur loading of Examples 1-7 is higher than that of Comparative Example 1, indicating that the sulfur loading of the composite SPAN electrode material doped with ZIF-derived transition metal sulfide is improved, because the addition of transition metal elements enhances the cross-linking effect between PAN and S, and PAN fixes more S.

[0048] The sulfur loading amount of Example 2 is different from that of Example 4. This is because the surface additive CTAB changes the morphology of ZIF-derived CoS2 and indirectly changes the cross-linking effect between PAN and S, affecting the performance of the electrode material.

[0049] The sulfur loading in Example 2 is higher than that in Example 5 and Example 6, indicating that too high or too low mass ratio of SPAN to CoS2 will affect the sulfur loading of the composite material. The sulfur loading in Example 7 is slightly higher than that in Example 3, further indicating that increasing the content of transition metal sulfide can increase the sulfur loading.

[0050] Table 2 shows the cycle performance of Examples 1-7 and Comparative Example 1 at a current density of 0.3C. It can be seen from Table 2 that the initial discharge specific capacities of Examples 1-7 are all higher than those of Comparative Example 1, because the addition of transition metal sulfides enhances the conductivity of the electrode material, catalyzes the electrochemical reaction, and improves the kinetics of the redox reaction. The initial discharge specific capacity of Example 3 is 1452.6 mAh / g, which is higher than that of Examples 1 and 2, indicating that the bimetallic composite material can provide more reaction sites, and different transition metals have different effects on the performance.

[0051] Table 3 shows the long cycle performance of Examples 1-7 and Comparative Example 1 at 1C current density. The initial discharge specific capacities of Examples 1-7 are all higher than that of Comparative Example 1, and after 500 cycles at 1C, the capacity decay rate per cycle of each Example is significantly lower than that of Comparative Example 1. This shows that the addition of transition metal sulfides improves the electrochemical reaction kinetics, enhances the conversion efficiency of sulfur, and improves the long cycle performance. From the data of Examples 2, 5, and 6, it can be seen that the cycle stability of the battery is also optimized as the CoS2 content increases.

[0052] Figure 1 3 and 4 are EIS curves of Example 1, Example 2 and Comparative Example 1. It can be found from the figure that the resistance of Example 1 and Example 2 is significantly better than that of Comparative Example 1, indicating that after the transition metal sulfide is compounded, the reaction kinetics of the SPAN electrode material is improved and the overall conductivity of the battery is improved.

[0053] Table 1. Sulfur loading of different examples

[0054] sample Sulfur loading (%) Example 1 42.62 Example 2 43.55 Example 3 43.23 Example 4 42.12 Example 5 41.38 Example 6 38.72 Example 7 45.19 Comparative Example 1 38.33

[0055] Table 2. Cyclic performance of different embodiments at 0.3C

[0056] sample First cycle (mAh / g) 100th cycle (mAh / g) Example 1 1324.5 1015.6 Example 2 1377.8 1107.4 Example 3 1452.6 1112.3 Example 4 1308.2 1050.8 Example 5 1343.6 992.3 Example 6 1224.5 971.7 Example 7 1332.4 1053.1 Comparative Example 1 1208.9 812.5

[0057] Table 3. Long cycle performance of different embodiments at 1C

[0058]

[0059] In summary, the present invention utilizes transition metal sulfides derived from MOF materials to in-situ composite with SPAN, and by regulating the type of transition metal and the amount of surface additives added, utilizes the advantages of MOF materials such as adjustable morphology rules, and synthesizes SPAN-based composite materials with high sulfur loading, high cycle, high rate and low resistivity as positive electrode materials, which are used for lithium-sulfur battery positive electrodes, and significantly improve their electrochemical performance.

[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material, characterized in that: The method comprises the following steps: 1) mixing polyacrylonitrile, transition metal salt and CTAB in an organic solvent to obtain liquid A; dissolving 2-methylimidazole in an organic solvent to obtain liquid B; adding liquid B to liquid A to obtain ZIF-PAN; and 2) mixing ZIF-PAN and sulfur powder, ball milling the mixture, drying the mixture and calcining the mixture to obtain a positive electrode material.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: The transition metal salt is one of zinc nitrate hexahydrate and cobalt nitrate hexahydrate or a mixture of the two.

3. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 1), the mass ratio of CTAB to transition metal salt is (1-4): (2-100); preferably (1-4): (8-12); more preferably 1:8; The mass ratio of transition metal salt, 2-methylimidazole and polyacrylonitrile is (4-6):(10-30):(20-100); preferably (4-6):20:(20-100), and more preferably 4:20:

40.

4. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 2), the mass ratio of ZIF-PAN to sulfur powder is 1:(3-10); preferably 1:

5.

5. The method for preparing the positive electrode material according to claim 1, characterized in that: The calcination step in step 2) is heat treatment at 300-450° C. for 2-10 hours.

6. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 1), the organic solvent is methanol or DMF; the molecular weight of the polyacrylonitrile is 50,000 to 500,000 g / mol.

7. The method for preparing the positive electrode material according to claim 1, characterized in that: The method further comprises step 3) removing the floating sulfur on the surface; specifically, heating at 150-250° C. in a nitrogen atmosphere for 5-20 hours.

8. A positive electrode material obtained by the preparation method according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: Comprising the positive electrode material, conductive agent and binder as claimed in claim 7; Preferably, the conductive agent is super-p; preferably, the binder is PVDF; Preferably, the positive electrode sheet is prepared by the following method: the positive electrode material, the conductive agent and the binder are uniformly mixed to prepare a slurry, and then the slurry is uniformly coated on an aluminum foil, dried, and cut to obtain the positive electrode sheet.

10. A lithium-sulfur battery, characterized in that: It comprises the positive electrode sheet, negative electrode sheet, separator and electrolyte as described in claim 9.

Citation Information

Cited By

  • Sodium ion battery and preparation method and application thereof

    CN119905645A